The implementation of shadowing technique in English language learning and teaching - Chi, Hong Dong Anh (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2022)
In teaching and learning English, learners have always been encouraged to fulfill and master four skills namely listening, speaking, reading, and writing. Undoubtedly, both listening and speaking skills are the most fundamental ones in the English learning process. There are numerical methods to facilitate English learning and teaching to be worldwide acknowledged for every single skill but the shadowing technique is one of the latest terms that helps develop the language learners listening, speaking, and potentially reading skills simultaneously. In this paper, an overview of the shadowing method will be described as a tool to assist English learning and teaching procedures, especially for listening and speaking skills. Also, this paper ends with a discussion on how to implement shadowing techniques in EFL classroom settings.